Risk factors associated with pouch adenomas in patients with familial adenomatous polyposis - Ganschow, Petra; Hinz, Ulf; Schaible, Anja; Büchler, Markus W. (Diseases of the colon & rectum, 2018)
BACKGROUND: Restorative proctocolectomy with ileal pouch-anal reconstruction is the standard prophylactic surgical procedure for patients with familial adenomatous polyposis. However, several groups have reported the development of adenomas and even carcinomas within the ileal pouch. The predisposing factor was the time interval after pouch surgery in some studies, but it was the severity of the initial colonic disease and duodenal adenomatosis in others. - OBJECTIVE: The aim of this study was to further clarify the prevalence of pouch adenomas, clinical risk factors, and a possible phenotype-genotype relation in a large population of patients with familial adenomatous polyposis, as well as to analyze pouch adenoma-free survival. - DESIGN: This study was designed as a cohort study. - SETTINGS: This study was conducted in a specialized outpatient clinic at the University of Heidelberg. - PATIENTS: A total of 192 patients with familial adenomatous polyposis were included, and all of the available endoscopy reports after pouch surgery were screened for pouch adenomas. Additional clinical information was retrieved from the Heidelberg Polyposis Register. - MAIN OUTCOME MEASURES: This present study revealed 3 main independent risk factors for the development of pouch adenomas: age <18 years at the time of IPAA, male sex, and the presence of gastric adenomas. Secondary outcome measures were adenoma progression and overall pouch adenoma-free survival. - RESULTS: Pouch adenomas were detected in 46.9% of patients. Median follow-up was 12.8 years (interquartile range, 9.0-17.0 y) for patients with pouch adenomas and 7.3 years (interquartile range, 2.5-12.2 y) for those without them. Patients underwent pouch surgery at a median age of 27.5 years (range, 10.2-58.5 y), and pouch adenomas occurred a median of 8.5 years (range, 0.9-25.1 y) after surgery. Also detected were gastric adenomas in 37.2%, duodenal adenomas in 80.3%, and desmoid tumors in 24.5% of patients. Estimation of pouch adenoma-free survival revealed that, after 20 years, only ≈22% of patients would be free of pouch adenomas. Male sex, age ≦18 years at the time of pouch surgery, and gastric adenomas were found to be independent risk factors for the development of pouch adenomas in a multivariate Cox regression analysis (p = 0.0002, p = 0.0059, and p = 0.0020). No predisposing germline mutation for pouch adenoma development was detected. - LIMITATIONS: Detailed information on the initial preoperative findings was not fully available, and the study was only carried out as a single-center study. - CONCLUSIONS: A severe upper intestinal phenotype, male sex, and age <18 years at the time of IPAA all increase the risk for development of pouch adenomas. See Video Abstract at http://links.lww.com/DCR/A675.
Gesehen am 09.12.2019